الإستراتيجيات المعاصرة لإدارة الموارد البشرية وعلاقتها بتحسين أداء المؤسسات الاقتصادية: دراسة حالة مجمع صيدال لصناعة الأدوية - أحمد، يوسف Ahmed, Yousuf; دلهوم، محمد الأمين Dalhoum, Mohammed Alamin (جامعة زيان عاشور بالجلفة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2019)
هدفت هذه الدراسة إلى التعرف على علاقة الاستراتيجيات المعاصرة لإدارة الموارد البشرية في تحسين أداء المؤسسات الاقتصادية الجزائرية من خلال دراسة حالة مجمع صيدال لصناعة الأدوية، حيث ركزنا على أهم الاستراتيجيات التي قامت بها إدارة الموارد البشرية اتجاه مواردها من أجل تحسين الأداء الكلي لمجمع صيدال، كما قمنا بتحليل أهم البيانات التي تحصلنا عليها من مديرية الموارد البشرية لمجمع صيدال والمتعلقة بالموارد البشرية، كما اعتمدنا في دراستنا هذه على المنهج اكي في الجانب النظري ومنهج دراسة الحالة في الجانب التطبيقي. وتوصلت الدراسة على أنه يوجد أثر للاستراتيجيات المعاصرة لإدارة الموارد البشرية في تحسين أداء مجمع صيدال لصناعة الأدوية وقدمت الدراسة توصية شاملة على ضرورة التركيز على الموارد البشرية التي والتركيز أكثر على رفع أداء الوحدات التنظيمية مع الاهتمام بتحليل بيئة الأعمال لأن لها تأثير مباشر على الأداء الكلي للمجمع.
The aim of this study was to identify the relationship of contemporary strategies of human resources management to improve the functioning of the Algerian economic institution through a case study saidal compound of the pharmaceutical industry. where we focused on hte major strategies of the department of human resources towards its resources to improve the overall perfomance of saidal compound. where we have the analysis of the most important data that we have obtained from the directorate of human resources of the complex saidal and human resource. and in our stuty we adopted this approach on cadastre in theory. and a case study on the ground and the study. However. ther is a trace of contemporary stratgies of human resources management in improving the performancce of saidal pool of pharmaceutical industry. The study provided comprhensive recommendations on the need to focus on human resources that are highly qualified and put more emphasis on raising the performance of the human resources and organizational units with the performance of interest in analysing the business environment as a direct impact on the overall performance of the compound.
Keywords: الإدارة -- إدارة الموارد البشرية -- أداء المؤسسات الاقتصادية -- مجمع صيدال لصناعة الأدوية